Does adding markers increase the accuracy and efficiency of intraoral scanning of complete dentures? - Lu, Jiayi; Yu, Jiayi; Saglik, Berna; Li, Junying (Journal of Prosthetic Dentistry, 2026)
Scanning a complete denture with an intraoral scanner has become an integral part of contemporary dental workflows, particularly for a digitally fabricated denture. However, whether the efficiency and accuracy of denture scanning can be improved by adding markers is unclear. The purpose of this study was to evaluate a new workflow and investigate whether it could optimize the efficiency and accuracy of a denture scan using an intraoral scanner. Two groups of denture scans were generated from a standard maxillary complete denture for comparison. In Group NM (no markers), the denture was scanned 20 times with an intraoral scanner using a consistent scan strategy. In Group WM (with markers), polyvinyl siloxane markers were added onto the denture as scan-aids, followed by 20 scans using the same scan strategy. A reference scan was obtained by using a desktop scanner (D2000). Test scans were aligned to the reference model using a best-fit algorithm in the exocad software program, excluding the cameo surface. The intaglio surface and 1 mm beyond the denture border were cropped and saved as a combined surface. This surface was further segmented into 4 critical regions: the denture border, posterior palatal seal zone, ridge area, and palatal area. Root mean square (RMS) values were calculated for the combined surface and segmented areas to assess accuracy. Scanning time, failure rate, and the number of 3-dimensional (3D) images were also recorded. Statistical analysis was performed using the Mann-Whitney U test and Levene test to compare trueness, scanning time, and the number of 3D images between the 2 groups (α=.05). Color mapping was used to visualize the surface deviations. Group WM demonstrated significantly better trueness and precision than Group NM across all evaluated regions. The mean RMS deviation for the combined surface was 37.6 µm in Group WM compared with 47.1 µm in Group NM (P <.001). Among the segmented areas, the posterior palatal seal zone exhibited the largest improvement in Group WM, with a mean RMS deviation of 60.8 µm compared with 86.5 µm in Group NM. Precision was also significantly enhanced, with Group WM achieving an RMS standard deviation of 2.9 µm for the combined surface compared with 9.8 µm in Group NM (P <.001). Scanning times were shorter in Group WM (122 ±12 seconds) compared with Group NM (143 ±16 seconds, P <.001), and the failure rate was markedly lower (1/20 in Group WM and 7/20 in Group NM). Additionally, Group WM captured significantly fewer 3D images than Group NM (2326 ±204 and 2782 ±268, P <.001). The addition of polyvinyl siloxane markers significantly enhanced the trueness and precision of scanning the maxillary complete denture while reducing the scanning time and number of 3D images. These findings highlight the potential of this approach to enhance the efficiency and reliability of complete denture digitization.